2015
DOI: 10.19070/2326-3350-si01001
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Feasibility, and Biomarker Effects of High-Dose Vitamin D Supplementation Among Women at High Risk for Breast Cancer

Abstract: Vitamin D deficiency is a potentially modifiable risk factor that may be targeted for breast cancer prevention. We examined the safety, feasibility, and biomarker effects of high-dose vitamin D among women at high risk for breast cancer. Forty high-risk women, defined as a 5-year breast cancer risk ≥1.67% per the Gail model, lobular or ductal carcinoma in situ, were assigned to a 1-year intervention of vitamin D3 20,000 IU or 30,000 IU weekly. Participants were monitored for toxicity every 3 months, underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Moreover, when vitamin D was administered to humans, IGF-1 levels in the blood increased [33]. On the other hand, another study showed that one year of high-dose vitamin D supplementation did not significantly alter serum IGF-1 among women at a high risk of breast cancer [34] nor in prediabetes subjects [35]. Our results revealed that patients in the SUF group had higher serum IGF-1 level than patients in the DEF and SUPL groups, both before and after the supplementation period.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when vitamin D was administered to humans, IGF-1 levels in the blood increased [33]. On the other hand, another study showed that one year of high-dose vitamin D supplementation did not significantly alter serum IGF-1 among women at a high risk of breast cancer [34] nor in prediabetes subjects [35]. Our results revealed that patients in the SUF group had higher serum IGF-1 level than patients in the DEF and SUPL groups, both before and after the supplementation period.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D supplementation in extremely high doses in mice increases susceptibility to colitis,83 and vitamin D supplementation in lethal doses in rats causes sloughing of the intestinal villi 84. In humans, supplementation in extremely high doses can have negative effects on digestion as exhibited through constipation 85,86…”
Section: Discussionmentioning
confidence: 99%
“…Our MR results suggesting that 25(OH)D does not have a causal effect on IGFBP-3 levels in the circulation are in agreement with the results from a randomized phase II trial of men with localised PCa and high grade prostatic intraepithelial neoplasia which found that supplementation with the vitamin D analog,1-alpha-hydroxyvitamin D2, did not have an effect on circulating IGFBP-3 levels 49 . Another vitamin D supplementation trial conducted among women with high risk of breast cancer also found little evidence that circulating IGFBP-3 levels changed after supplementation with 25(OH)D 50 . This does not preclude that increasing the availability of 25(OH)D with supplementation may lead to increased production of 1,25(OH) 2 D within tissues that could then stimulate the local production of IGFBP-3 that is not detected in the circulation.…”
Section: Discussionmentioning
confidence: 99%